Research Progress on the Reaction of Carbon Dioxide with Hydrazones and Their Derivatives - Hong-Xia Sun; Shao-Xuan Gong; Hong-Yang Zhang; Yu-Ting Liu; Li-Ling Shi; Yong-Jie Zhu; Xiu-Mei Xie; Jun-Jie Li; Jing Wen; Yong-Chang Guan; Zhen Zhang; Miao Zhang; et al. (Molecules)
CO2, an abundant and renewable C1 source, presents significant potential for applications in organic synthesis. Hydrazones, recognized for their distinctive properties, exhibit high versatility in synthetic chemistry, facilitating numerous chemical transformations. Given their crucial roles in organic synthesis, the combination of CO2 with hydrazones has garnered increasing research interest. This review provides a comprehensive summary of recent progress in reactions involving CO2 and hydrazones or their derivatives. These include the coupling of amines and N-tosylhydrazones with CO2, the umpolung-mediated carboxylation of hydrazones/N-tosylhydrazones with CO2, the cyclization of hydrazones with CO2, and lactamization reactions incorporating N-tosylhydrazones and CO2. These transformations utilize the diverse reactivity of hydrazones and their derivatives to capture and convert CO2, generating valuable organic compounds with both academic and practical relevance. Additionally, the review examines the mechanisms underlying these reactions, offering critical insights for advancing research in this area.